Mecanismos sócio-genéticos da representação social de trabalho docente por grupos de licenciandos de física e de química da Universidade Federal do Rio Grande do Norte - Braz, Márcia Cristina Dantas Leite (2013)
This research aims to understand the social representations Teaching Work in groups of undergraduate students of Physics and Chemistry of the Federal University of Rio Grande do Norte. For this, the proposal was based on the three theoretical and methodological consensus Carvalho (2012) in the explanation of socio-genetic mechanisms constituents of dynamic consensus that has functionality to your organization. It Was used to achieve this goal, the theoretical-epistemological Serge Moscovici (1978, 2003), Jodelet (2011), Wagner (1998,( 2011) and Carvalho (2012). The corpus analyzed results from a qualitative and quantitative research, developed in three stages. The first two (2) questionnaires to fifty (50) of each undergraduate course, a questionnaire and another profile for collection of free associations concerning motes inductors "Give Lesson," "Student" and "Teacher". The second step in the procedure Multiple Classifications, Roazzi (1995), aimed for another thirty (30) undergraduate students for each course, as well as Document Analysis of Educational Projects Curriculum courses in Physics and Chemistry. The data analysis of the first stage focused on descriptive statistics and frequency and average order of the words associated with motes inductors. The results from the Multiple Classification Procedure submitted to multidimensional analysis (MSA multidimensional scalogram analysis) and SSA (Similarity Structure Analysis), were interpreted by the theoretical and methodological proposal of the three consensus, supported by analysis of the rhetorical nature of justifications classifications and categorizations of words, boosted in times of application of Procedure Multiple Classification. The data revealed that the groups surveyed were the same Social Representation with specific dynamic consensual. Thinking Teaching Work for these groups it is considered in three dimensions: the BE-DO-HAVE of teaching. In the group of Physics consensus was clear semantic, which expressed a dynamic in which the interpretations of "Teaching Work" peacefully coexist on perceptions of two concepts: An identity around the "BE" "Teacher" or "BE" "Educator" and the other, how they think about professional development. The type of group consensus Chemistry pointed to a consensual logic hierarchical order in which the gradual between the elements of BE-DO-HAVE attested conflicts and disagreements about the perceptual object "Teaching Work", around what value most, whether they are the attributes of personal or professional-technical dimension of teaching, in the course of professional development. The thesis to explain the mechanisms of socio-genetic Representation Social Teaching Work by theoretical and methodological proposal was confirmed